2016
DOI: 10.1083/jcb.201603080
|View full text |Cite
|
Sign up to set email alerts
|

Formin-generated actomyosin arcs propel T cell receptor microcluster movement at the immune synapse

Abstract: Murugesan et al. report that actomyosin arcs at the T cell synapse are formin-generated structures that directly propel T cell receptor cluster movement. The authors reveal the origin, organization, and functions of a major cytoskeletal network during synapse maturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
303
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(335 citation statements)
references
References 62 publications
31
303
1
Order By: Relevance
“…The polarized filopodia structures formed after GML treatment are phenotypically similar to structures found in Arp2- and Arp3-deficient T cells or T cells treated with Arp2/3 inhibitors (8, 9). To determine whether GML induced filopodia formation by inhibiting Arp2/3 complex activity, we used the small molecule inhibitor CK-666, which stabilizes the inactive state of the Arp2/3 complex by preventing the Arp2 and Arp3 subunits from moving into the activated filament-like conformation (47).…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…The polarized filopodia structures formed after GML treatment are phenotypically similar to structures found in Arp2- and Arp3-deficient T cells or T cells treated with Arp2/3 inhibitors (8, 9). To determine whether GML induced filopodia formation by inhibiting Arp2/3 complex activity, we used the small molecule inhibitor CK-666, which stabilizes the inactive state of the Arp2/3 complex by preventing the Arp2 and Arp3 subunits from moving into the activated filament-like conformation (47).…”
Section: Resultssupporting
confidence: 52%
“…Formins bind to the barbed edge of actin filaments and prevent the association of actin with actin-capping proteins (7). Formins regulate the assembly of structures in the pSMAC and are critical for the retrograde flow of signaling clusters into the cSMAC (8, 9). In contrast, the activated Arp2/3 complex mediates the branching of actin filaments that ultimately drives the formation of the dense lamellipodia structures in the dSMAC (8, 10).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent in vitro studies have shown that formins bind to MTs through their FH2 domain, which suppresses the actin polymerization function of formins (48,49), although the formin mDia1 was also reported to polymerize actin filament by recruitment to MT tips (50). In addition, a recent study showed that NMII-rich actin arcs in the IS are derived from formin-mediated actin polymerization primarily in the lamellipodia (51). To test whether the activation of ROCK and formin mediates MT-actin interactions at the T-cell contact zone, we activated EB3-EGFP-and TagRFP-Tactin-expressing Jurkat cells on anti-CD3-coated coverslips in the presence of Y-27632 or the formin inhibitor SMIFH2 (15 μM) (52).…”
Section: Mt Network Forms a Radially Emanating Dynamic Array During Tmentioning
confidence: 99%
“…Actin polymerization and myosin contraction induced by TCR engagement results in retrograde flow of actomyosin at the cell periphery which serves as a primary force-generating element at the cell-substrate interface. The advent of super-resolution imaging and novel fluorescent probes has revealed a diversity of actin structures at the T cell/substrate interface [56]. On planar substrates (and conjugates), within 2–3 minutes of stimulation, the actin network forms an annular ring at the lamellipodium and is composed of the characteristic Arp2/3 mediated branched networks as well as formin-mediated linear bundles.…”
Section: Cytoskeletal Dynamics During Immune Cell Activationmentioning
confidence: 99%